EP-351 Extended VTE prophylaxis in patients undergoing elective surgery for colorectal cancer in a district general hospital and its Compliance with NICE guidelines. (9th August 2022) - Elzaafarany, Ahmed; Tawfik, Ahmed; Igbekele, Tosin; Day, Andrew
Abstract: Aim: A This audit aims to assess the department's current compliance with guidance, understand reasons for non-adherence and implement a plan of action to improve future compliance and subsequent patient outcomes. Background: NICE guidance recommends extended VTE prophylaxis for up to 28 days post colonic resection for cancer Methods: A single centre, retrospective, observational study was performed between January 2018 –January 2019. We included all the Patients who underwent elective colorectal resections for cancer. Results: A total of 123 patients had elective elective colorectal resections for cancer. 91 (73%) were laparoscopically, 8 (6.5%) laparoscopic converted to open and 24 (19.5%) were done as open operations from the start. The summary of the operations done were as follows; 62 RHC, 25 HAR and 36 LAR. LMWH for extended VTE prophylaxis for 28 days was prescribed for 91% (112/123) of the patients among the studied period. 5.7% (7/123) were already receiving alternative anticoagulation thus the NICE guidance was achieved for 96.7% (119/123). The patients who did not receive VTE prophylaxis were 3.3%, 4/123), there was no clinical reason documented or identified for this omission. A postoperative VTE was experienced in 4.8% (6/123), 3 of them required a hospital admission (50%). There was no VTE related mortality documented Conclusion: This audit has demonstrated 96.7% of patients who underwent surgery for colorectal cancer received extended VTE prophylaxis as per NICE guidelines. This is a significant improvement from previous audit cycle, though the aim is for 100% compliance with guidelines. We implement plan of action to achieve that